(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2017)
The objective of the study was to identify the grafting method, which will have a higher success rate of scion development. The study was conducted at Mount Makulu Central Research station in Chilanga, Zambia (15o33S / 28o11E) from April 2010 to November 2011. The study had 4 vegetative propagation methods that varied in the treatment of the rootstock and scion. The four methods were Standard T- budding (STB); Modified TBudding with decapitation (TBD); T- budding with scion bending (TBB); Crown grafting (CG). Bud take, shoot growth, leaf emergence and Leaf area index were measured up to 11 weeks after treatment (WAT). With CG there was 100 % bud take. STB had a bud take of 58.3 %. TBD had a bud take of 50 %. The lowest bud take percentage was recorded in TBB, which had a bud take of 41.7 %. At 5 weeks the STB and TBB treatment had shoot length of 0.7 and 1.0 cm respectively which were the shortest; this was followed by the CG treatment at 15.3 cm and the modified TBD with apical shoot decapitation (21.7 cm). STB shoots did not start growing until about 5 weeks, which was 2 weeks after the rootstock was cut off. At 5 weeks, the TBB and STB were yet to form leaves. The CG had close to 20 leaves and the TBD had almost 15.2 leaves. At the end of 11 weeks, the TBB had the highest number of leaves. Across the grafting methods; the Leaf area exhibited a pattern similar to leaf number; it kept on doubling every 2 weeks to until the 9th week after which the increase was negligible. At 11 weeks, the highest leaf area was in the TBD followed by the STB and lowest in the CG treatment. Int. J. Agril. Res. Innov. & Tech. 7 (1): 64-70, June, 2017